Efisiensi Mesin Diesel Pada Tambak Udang Dengan Eksperimen Desain - Nicholas Handoko; Indriati Njoto Bisono (Jurnal Titra, 2015)
The operational cost to operate paddle wheel with generator at PT X is very high; for daily shrimp cultivation each farm need 14 paddle wheels that use 24 hours electricity from the generators. Thus an experiment was conducted to minimize the number of paddle wheels operated. Naturally, pond water contains phytoplankton that carries photosyntesis to produce oxygen at noon. Photosyntesis processes need carbon dioxide to turn to oxygen at noon, on the other hand paddle wheel also need the carbon dioxide in the pond and turn it into oxygen. Thus the two are conflicted. Turning off the paddle wheels at noon then increase the photosynthesis process, make it more effective. The experiment results show that turning off paddle wheel at noon did not affect oxygen supply and the average weight of the shrimps.